Ecocritical Reading of Land and Landscape in Muhammad Haji Salleh’s Rowing Down Two Rivers: An eco-consciousness approach - Abdul Hamid, Nurul Huda; Ahmed Mohsen, Hamoud Yahya (EDUCATUM Journal of Social Sciences, 2024)
The Malaysian National Laureate Muhammad Haji Salleh has always been true to his green roots. Even when things are hard, he finds comfort and interest in Motherland’s embrace. This paper is aimed to highlight the identity-land symbiotic interconnectedness in Muhammad Haji Salleh’s selected poems through the lens of ecocriticism. In the selected poems we examined the concept of eco-consciousness with the purpose of to better understand how Muhammad Haji Salleh view the concept of personal identity as intrinsically tied to the natural world. Upon detailed analysis of the selected poems, it becomes evident that Muhammad Haji Salleh has never ceased preaching about the plight of the Malaysian land and landscape and the urgent need for worldwide attention. His poetry proves that he utilizes the land and landscape as an iconic form of aspiration and even ecocritically functional and through the application of the concept of eco-consciousness, the researchers conclude that while there are strong and deep connections between humans and their land and landscape, this does not change the fact that humans are more dependent towards nature than vice-versa. The researchers believe that reading more poems by Muhammad Haji Salleh and other Malaysian poets will produce a better and more thorough finding for future research on the topic of the inextricable connection between individual identity and the natural world. Thus, this study shows the implications of developing Malaysian ecocriticism as a means to read literature and to understand the significance of the land-identity attachment in the psyche of Malaysians.